Analisis Pengaruh Manajemen Modal Kerja terhadap Profitabilitas dalam Industri Consumer Goods yang Terdaftar di Bursa Efek Indonesia - Iswandi Iswandi (Binus Business Review, 2012)
In this paper we evaluate the relathionship between working capital management and corporate profitability. We used a sample of 29 companies in consumer goods industry listed in the Bursa Efek Indonesia for the period of 2006 – 2008. The results of the evaluation showed that there is statistical significance between profitability, measured through gross profit, and the cash conversion cycle. Empirical findings show that NDAR, NDI, NDAP affect firm profitability negatively, while CCC affects firm profitability positively.